Twisted tensor products of K 3 with K 3 - Arce J. (2021)
Jorge A. Guccione and Juan J. Guccione were supported by UBACyT 20020150100153BA (UBA) and PIP 11220110100800CO (CONICET). This work was supported by CONCYTEC-FONDECYT within the framework of the contest ?Proyectos de Investigaci?n B?sica 2020-01? [contract number 120-2020-FONDECYT].